2017
DOI: 10.4103/ccd.ccd_836_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze dried powdered probiotics on gingival status and plaque inhibition: A randomized, double-blind, parallel study

Abstract: Objective:The study aimed to evaluate the effectiveness of freeze dried powdered probiotics on gingival status and plaque inhibition among 12–15-year-old schoolchildren.Materials and Methods:This randomized controlled trial was conducted among 12–15-year-old schoolchildren in Jaipur. Commercially available freeze dried probiotics containing Lactobacillus acidophilus, Bifidobacterium longum, Bifidobacterium bifidum and Bifidobacterium lactis (Prowel, Alkem Laboratories), lactic acid bacillus only (Sporolac, San… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In addition, B. longum could be used as a psychobiotic since it attenuates the physiological and psychological response to acute and long-term stress situations with a subtle improvement in visuospatial memory [ 36 ]. Furthermore Yousuf et al (2017) demonstrated that a daily used probiotic mouth rinse containing B. longum and other strains, reduced plaque accumulation and gingival inflammation in schoolchildren [ 37 ]. It is of importance that our study demonstrated that this beneficial bacterium is inhibited by the antimicrobial peptide nisin, which is produced by L. lactis .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, B. longum could be used as a psychobiotic since it attenuates the physiological and psychological response to acute and long-term stress situations with a subtle improvement in visuospatial memory [ 36 ]. Furthermore Yousuf et al (2017) demonstrated that a daily used probiotic mouth rinse containing B. longum and other strains, reduced plaque accumulation and gingival inflammation in schoolchildren [ 37 ]. It is of importance that our study demonstrated that this beneficial bacterium is inhibited by the antimicrobial peptide nisin, which is produced by L. lactis .…”
Section: Discussionmentioning
confidence: 99%
“…27 L. acidophilus and Bifidobacterium inhibit the growth of periodontopathogens like P. gingivalis 28 and significantly reduced gingival inflammation and plaque accumulation in school children. 29 A combination of lactobacillus strains (L. reuteri, salivarius and acidophilus) demonstrated significant reduction in pocket, bleeding on probing and attachment gain in severe periodontitis patients. 30 Lactobacillus rhamnosus, is found to inhibit gram-negative periodontal pathogens in in vitro studies.…”
Section: Ta B L Ementioning
confidence: 99%
“…lactis DN-173010 had a positive effect on gingival inflammatory parameters after a 5-day non-brushing period. In a study by Yousuf et al [9], plaque index (PI) and gingival index (GI) scores were reduced in adolescents after two weeks administration of a probiotic combination containing Bifidobacterium longum, Lactobacillus acidophilus, Bifidobacterium bifidum, Bifidobacterium lactis and acid lactic bacillus. Dhawan and Dhawan [11] showed a significant reduction of PI up to 4 weeks with the probiotic combination Lactobacillus sporogenes, Streptococcus faecalis PC, Clostridium butyrium TO-A, and Bacillus mesentericus TO-A in patients with gingivitis.…”
Section: Probiotics In Gingival Health and Gingivitismentioning
confidence: 99%
“…Overall, these studies suggest that long term use of some probiotics may aid in oral hygiene, promote gingival health, and help to treat gingivitis. This effect is more significant when there is no mechanical removal of the plaque [4,7,9,11,38,40] than when the plaque is removed [35]. Additional long-term studies are needed in larger population across all age ranges and ethnic groups to obtain more consistent clinical results, and to determine if probiotics need to colonize the oral cavity to cause a beneficial effect.…”
Section: Probiotics In Gingival Health and Gingivitismentioning
confidence: 99%
See 1 more Smart Citation